Protection Against Mobbing in Labor Relations: Problems of Legal Regulation - O. A. Kursova (Сибирское юридическое обозрение, 2014)
. In the current article an attempt is made to present the basic views on the problems of legal regulation in the sphere of legal protection against psychological violence at work.